On the Beat of Truth : A Hearing Daughter's Stories of Her Black Deaf Parents - Brown, Maxine Childress (Book collections on Project MUSE., 2013)
As an African American woman born in 1943, the author possessed a unique vantage point to witness the transformative events in her parents' lives. Both came from the South - her father, Herbert Childress, from Nashville, TN, and her mother, Thomasina Brown, from Concord, NC. The oldest of three daughters, Maxine was fascinated by her parents' stories. She marveled at how they raised a well-respected, middle-class family in the midst of segregation with the added challenge of being deaf. Her parents met in Washington, DC, where they married and settled down. Her father worked as a shoe repairman for $65 per week for more than 15 years. A gifted seamstress, her mother gave up sewing to clean houses. Because of their modest means, Maxine and her sisters lived more than modest lives. When Maxine's tonsils became infected, her parents could not afford the operation to have them removed. For her high school prom, her mother bought her a dress on credit because she had no time to sew. Herbert Childress showed great love for his young daughters, but difficult events turned him to bitterness and to drink. Throughout all, Thomasina encouraged her girls, always urging them to excel. She demanded their honest best with her signature phrase, her flat hand raised from her mouth straight up in the air, "on the beat of truth."